An energy harvesting system for time-varying energy transducers with FOCV based dynamic and adaptive MPPT for 30 nW to 4 mW of input power range. (August 2021) - Saini, Gaurav; Baghini, Maryam Shojaei
Abstract: This article, for the first time, presents an energy harvesting system (EHS) for harvesting the energy from the continuous time-varying energy harvesters using the fractional open-circuit-voltage (FOCV) based dynamic and adaptive maximum power point tracking (MPPT). The proposed EHS includes an energy harvester, a start-up circuit, a DC-DC boost converter, a DC-DC buck converter, and a control circuit. In the FOCV based MPPT, a fraction of the open-circuit-voltage (OCV) of the energy harvester, is maintained at the output of the energy harvester (input of a DC-DC boost converter). In the proposed work, OCV of the energy harvester is dynamically and adaptively sampled depending on the ambient conditions and the maximum available power from the energy harvester. This helps in improving the tracking efficiency of the proposed MPPT circuit for the time-varying energy harvester by more than 10 % . The boost converter switching time period instants are utilized for sampling the OCV of the energy harvester. A 12-stage Dickson based charge pump along with a 5-stage ring oscillator with a modified clock distribution is used for the start-up. Post-layout simulated results of the proposed EHS are presented in the 180 nm mixed-mode CMOS technology. The tracking efficiency and the boost converter efficiency for a wide range of the available input power (30 nW to 4 mW ) compatible with many time-varying ambient energy harvesters in both indoor and outdoor places are presented. For a time-varying energy harvester, the tracking efficiency is more than 96% . For a source resistance of 100 kΩ, the boost converter's efficiency is 60.09% and 90.77% at available power of 56 nW and 1.6   μ W, respectively.